Β-N-methylamino-l-alanine is a non-competitive inhibitor of vesicular monoamine transporter 2. (15th January 2023) - Kennedy, Chanté; van Onselen, Rianita; Downing, Tim G.
Abstract: The neurotoxic, non-proteinogenic amino acid β- N -methylamino-l -alanine (BMAA) has been implicated in the development of neurodegenerative diseases; however, the mechanism(s) and mode(s) of toxicity remain unclear. Similarities in the neuropathology and behavioural deficits of neonatal rats exposed to either BMAA or reserpine, a known vesicular monoamine transporter 2 (VMAT2) inhibitor, suggest a similar mode of action. The aims of this study were therefore to determine if BMAA could prevent the uptake of serotonin into dense granules via inhibition of VMAT2, and, if so, the type of inhibition caused by BMAA. Exposing platelet dense granules to BMAA resulted in a concentration-dependent reduction in serotonin uptake. The inhibition of VMAT2 was non-competitive. The findings from this study support previous reports that BMAA-associated neuropathologies in a neonatal rat model may be due to VMAT2 inhibition during critical periods of neurogenesis. Graphical abstract: Image 1 Highlights: BMAA is a potent inhibitor of VMAT2. BMAA is a non-competitive VMAT2 inhibitor. The binding of BMAA to VMAT2 may be via essential hydroxyl groups on the transporter.